2022
DOI: 10.3390/foods11223650
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Some Spaghetti Processing Variables on Technological Attributes and the In Vitro Digestion of Starch

Abstract: Durum semolina spaghetti is known to have a low-moderate glycaemic index but the impact of various processing variables during the manufacture and cooking of pasta does affect pasta structure and potentially could alter starch digestion. In this study, several process variables were investigated to see if they can impact the in vitro starch digestion in spaghetti while also monitoring the pasta’s technological quality. Cooking time had a large impact on pasta starch digestion and reducing cooking from fully co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…Jurkaninová et al [41] found that the content of resistant starch in dumplings increased with the time they were stored at low temperatures (about 5 ⁰C). On the other hand, according to Sissons et al [42], cold storage of cooked pasta was expected to increase retrograded starch but the increase in resistant starch was minor with no consequent improvement in the extent of starch digestion.…”
Section: Types Of Resistant Starchmentioning
confidence: 98%
See 1 more Smart Citation

Digestibility of starch

Šárka,
Smrčková,
Sluková
2024
Preprint
“…Jurkaninová et al [41] found that the content of resistant starch in dumplings increased with the time they were stored at low temperatures (about 5 ⁰C). On the other hand, according to Sissons et al [42], cold storage of cooked pasta was expected to increase retrograded starch but the increase in resistant starch was minor with no consequent improvement in the extent of starch digestion.…”
Section: Types Of Resistant Starchmentioning
confidence: 98%
“…Sissons et al [42] suggested subtly manipulating the starch digestion of pasta through some processing procedures. Cooking time had a large impact on pasta starch digestion and reducing cooking from fully cooked to al dente and using pasta of very high protein content (17%), reduced starch digestion extent.…”
Section: How To Increase Digestion Of Starchmentioning
confidence: 99%

Digestibility of starch

Šárka,
Smrčková,
Sluková
2024
Preprint
“…One of the parameters contributing the greatest to consumers' high demand for pasta is its quick cooking. The cooking time for the pasta is the required time to obtain a complete gelatinization of the starch (Sissons et al, 2022). The effect of MC and NFC on the CT at a constant ET = 107 °C is shown in Figure 2a.…”
Section: Cooking Time (Ct)mentioning
confidence: 99%